1986
DOI: 10.1063/1.337698
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of UV laser ablation of organic polymer surfaces

Abstract: A model based on a time-dependent treatment of the ablation of organic polymer surfaces by UV laser radiation is proposed. It relates the dynamics of the etching process to the experimental parameters such as the fluence, wavelength, and the width of the laser pulse. The model is applied to poly(methyl methacrylate) and to polyimide in order to predict the etch characteristics quantitatively and to compare them systematically to the experimental results. This model accounts for a wide variety of observations s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
0
4

Year Published

1989
1989
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(98 citation statements)
references
References 24 publications
2
92
0
4
Order By: Relevance
“…2 of [4]) with 248 nm excimer laser pulses shows for higher fluences a leveling off and reaches a saturation plateau, where a further increase in fluence does not yield a significantly higher etch rate. This effect had been attributed to a shielding of the PMMA surface by the ablation plume I- 5,6]. Our model calculations [-4] showed, however, that this alone could not fully explain the effect.…”
mentioning
confidence: 66%
“…2 of [4]) with 248 nm excimer laser pulses shows for higher fluences a leveling off and reaches a saturation plateau, where a further increase in fluence does not yield a significantly higher etch rate. This effect had been attributed to a shielding of the PMMA surface by the ablation plume I- 5,6]. Our model calculations [-4] showed, however, that this alone could not fully explain the effect.…”
mentioning
confidence: 66%
“…Unlike nanosecond laser irradiation at longer wavelengths, thermal effects are negligible in 193 nm laser photochemistry of polymer surfaces, and the thermal effects increase with the incident wavelength. 27 Oman et al 28 estimated the maximum temperature increase of a graphite surface illuminated by 193 nm light at a fluence of 0.1 J/cm 2 to be approximately 160 K. Although polystyrene has a relatively low melting point (∼550 K), particle heating to the melting point does not likely occur, as several researchers reported that there is no evidence that the surface has melted or flowed even in a polymer with a glass temperature as low as 400 K; they concluded that photochemical etching is the dominant mechanism in 193 nm laser irradiation of polystyrene and other polymer surfaces. [29][30][31] In our previous study, carbon atom fluorescence was measured from polystyrene and soot particles using 193 nm photochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…In micromachining of polymers, the excimer laser ablation of polymer materials has been investigated by various researchers in last few decades Sutcliffe 1986;Kuper 1987;Bruan 1989;Rumsby 1991;Gower 1992). It has been observed that the interaction of pulsed high repetition excimer laser with polymer surface leads to ablative photo-decomposition which results basically due to etching of polymer surface and explosive ejection of decomposition products at supersonic velocities (Callewaert 2003).…”
Section: Excimer Laser 2d/3d Patterningmentioning
confidence: 99%